FORMULATION AND EVALUATION OF DICLOFENAC SODIUM MICROSPHERES FOR STABILIZATION OF DICLOFENAC (International Journal of Food and Nutritional Sciences, 2019)
Chemical entities known as drugs should pass the physicochemical properties to satisfy thecategory of drug. It should be stable and should exhibit its activities devoid of undue adverseeffects. It was observed that very common drug diclofenac sodium degrades in aqueous mediaat a drastic rate. In the present study, we evaluated the ways to shield the diclofenac sodiumwhich can delay the degradation or release and thereby increasing its efficacy.In the presentwork diclofenac sodium microspheres were prepared using various polymers like gelatin, ethylcellulose by using solvent evaporation and ionic gelation methods.